Leadership style and organisational performance through innovation technology within Abu Dhabi police in UAE - Al Derei, Hamad Salem Saeed (2023)
It is recognized that managers play a significant role in organizational performance, work improvement, and employee satisfaction. Leadership styles give managers the ability to make decisions, work collaboratively, or delegate tasks to their employees. The United Arab Emirates (UAE) aims to be one of the most effective countries in the world, and to this end, they have created various programs to encourage the government to develop leadership capabilities and enhance performance through monitoring and creating several excellence awards. The Abu Dhabi Police face unique challenges in terms of coordinating employee work effectively over the next few decades. This trend presents new problems for leaders, as they are expected to increase their innovativeness at the same time. This research discusses and analyzes the impact of leadership styles on organizational performance through innovation technology within the Abu Dhabi Police in the UAE. This study utilized simple random sampling to collect the data. The study validates the proposed conceptual framework using a second-order confirmatory factor analysis technique, namely, structural equation modeling, and then uses smart PLS with data collected from 320 employees in the criminal investigation and security sector in the UAE. According to the findings, transformational and transactional leadership have a positive and significant effect on organizational performance. Moreover, innovation technology has a partial mediation effect on the association between leadership styles and organizational performance. This research contributes to the academic understanding of the influence of transformational and transactional leadership on innovation technology, which may impact employee excellence and organizational performance, particularly in the context of the Abu Dhabi Police in the UAE. It is proven that leadership styles are significant for the police sector, benefiting the accomplishment of its goals and improving organizational performance. The study also recommends that regulatory bodies responsible for regulating Abu Dhabi Police in the UAE provide standard guidelines and encourage all police to implement leadership styles properly to achieve organizational performance.